The Power of City Branding in Enhancing Solo City’s Competitiveness as an International Destination - Halifa Haqqi; Hasna Wijayati; Andika Drajat Murdani (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines how city branding enhances Solo City’s international competitiveness through cultural identity and creative economy development.Research Methodology: A qualitative descriptive approach was applied using semi-structured interviews, field observations, and snowball sampling involving government officials, cultural institutions, and creative economy actors. Data were analyzed through thematic analysis.Results: Solo City strengthens its global positioning by utilizing cultural identity, local wisdom, international events, cultural symbols, creative products, and multi-stakeholder collaboration.Conclusions: Successful city branding depends on synergy among tourism attractions, public services, security, and government-community coordination.Limitations: This single-case qualitative study is limited by contextual scope, interpretive subjectivity, and the absence of international stakeholder perspectives.Contributions: This study contributes to city-branding literature by linking cultural capital, public diplomacy, and international competitiveness while offering practical insights for culturally based cities.